2010
DOI: 10.1111/j.1442-200x.2010.03195.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor γ 2 mutation may cause a subset of ulcerative colitis

Abstract: These findings suggested that imbalances between TLRs and PPARγ in response to luminal bacteria could lead to colonic inflammation in some UC patients. Alternative explanations will be needed for the onset of the rest of UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…As a representative negative regulator of the PRR-linked signals, the peroxisome proliferatoractivated receptor g (PPARg) mediates immune tolerance to bacteria-stimulated inflammation associated with colitis (10)(11)(12). Genetic ablation of PPARg is observed in patients with ulcerative colitis, which is associated with severe chronic inflammatory outcomes (10). As another regulatory transcription factor, activating transcription factor 3 (ATF3) is induced as part of the negative feedback loop that modulates PRR-stimulated inflammatory responses (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a representative negative regulator of the PRR-linked signals, the peroxisome proliferatoractivated receptor g (PPARg) mediates immune tolerance to bacteria-stimulated inflammation associated with colitis (10)(11)(12). Genetic ablation of PPARg is observed in patients with ulcerative colitis, which is associated with severe chronic inflammatory outcomes (10). As another regulatory transcription factor, activating transcription factor 3 (ATF3) is induced as part of the negative feedback loop that modulates PRR-stimulated inflammatory responses (13)(14)(15).…”
mentioning
confidence: 99%
“…As a representative negative regulator of the PRR-linked signals, the peroxisome proliferatoractivated receptor g (PPARg) mediates immune tolerance to bacteria-stimulated inflammation associated with colitis (10)(11)(12). Genetic ablation of PPARg is observed in patients with ulcerative colitis, which is associated with severe chronic inflammatory outcomes (10).…”
mentioning
confidence: 99%
“…Although TLRs signal transmit through the MyD88-dependent or -independent pathway, previous studies have indicated a significant role of the TLR-MyD88 pathway on IBD (15,25). Aoyagi et al have reported that mRNA levels of MyD88, TLR-4 and NF-κB p65 are significantly increased in colonic mucosa of UC patients (26). It has also been reported that the Myd88 protein level is increased in the colonic mucosa of non-treated UC and this increase is suppressed by azathioprine treatment (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no evidence regarding the function of rs7744. However, there may be a possibility of overexpressing the MyD88 protein in the rs7744 minor allele variants, considering overexpression of mRNA and protein levels of MyD88 in UC patients (15,26). There are binding sites of miR-150-3p and miR-1236 of 100 bp around rs7744.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…28 Recent studies have shown a significant association between deficiency of PPAR and IBD. 48 In addition, activation of PPAR could attenuate the inflammation in the gut. 49 These results suggest that colonic PPAR may be a promising therapeutic target in patients suffering from IBD.…”
mentioning
confidence: 99%